PENGGUNAAN MEDIA PEMBELAJARAN VIDEO YOUTUBE UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MENGGAMBAR ILUSTRASI SISWA DI KELAS VIIIE SMP NEGERI 1 PADANG - Nilam Cahayani, Dr. Ramalis Hakin, M.Pd., Yofita sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2017)
The purpose of this research were to : 1) increase student’s interest and learning outcomes on ilustration drawing lesson at VIIIE class in SMP Negeri 1 Padang, using the instructional media Youtube. The research was done by using The Class Action Research. The data were gathered by using observation student’s interest format, teacher’s observation, student’s interest questionnare and student’s assignment. Based on research was finding, the student’s interest in ciycle I was 80.15% and in cycle II increased becoming 92.06%. While the student’s average learning outcomes in cycle I was 81.00 and in cycle II increased becoming 91.00.Keywords:Media Video, YouTube. Interest, Learning Outcomes